The role of non-formal education in promoting the achievement of Sustainable Development Goals (SDGs) 4 - Wifaqi, Hikmah; Chamidah, Nur; Widyastuti, Annisa; Azharotunnafi, Azharotunnafi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Quality education is an important element in creating superior and competitive human resources. However, these efforts do not only rely on formal education, but are also supported by non-formal education, which plays a role in expanding access and lifelong learning skills. This study aims to analyze the role of non-formal education in promoting the achievement of Sustainable Development Goals (SDGs) 4 on point 7 at the FIB School of Talents Malang. This study uses a qualitative approach with a case study type. Data collection techniques include in-depth interviews, observation, and documentation study, while data analysis uses the Miles et al. model, which includes data condensation, data presentation, and conclusion drawing and verification. The results show that FIB School of Talents Malang has a strategic role in supporting the achievement of SDGs 4.7 in five main aspects: (1) fulfillment of human rights through equal access to education for all students; (2) implementation of gender equality by providing equal opportunities for men and women in digital learning; (3) internalization of anti-violence values by creating a safe and supportive learning environment; (4) strengthening global citizenship values through international collaboration; and (5) fostering appreciation for cultural diversity through collaborative learning activities. Thus, non-formal education has proven to be capable of supporting the creation of education in line with SDG 4 point 7. These findings reinforce the important role of non-formal education in strengthening the national education system and supporting the sustainable realization of SDG 4.